Girls on fire : a novel - Wasserman, Robin (New York, NY : Harper, 2016)
When a popular high school athlete commits suicide amid rumors of local satanic worship in a 1990s Pennsylvania community, an unlikely friendship between a lonely misfit and a pop-culture rebel leads both to a feverish downward spiral of high risk and dangerous secrets.
Keywords: Teenage girls -- Fiction; Pennsylvania -- Fiction; Bildungsromans; Suspense fiction